Food Service Quality of Canteen Concessionaires: an Assessment Towards Customer Satisfaction at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The importance of the school canteen is highlighted by the development of nutritious foodsand a desire among students to purchase a variety of foods. The Canteen can be helpfulamong the students when it comes to accessibility and the low budget price on the menu. Itcan be a problem for the students when it comes to the quality of food and the hygiene ofevery staff.According to the results of the surveys, many students agreed that the canteen in BSHM is ingood condition in terms of the quality of food, facilities, and staff. Every area of the canteen,especially the kitchen, where all the items that the students have ordered are processed,should be kept clean by the canteen staff. For the students to be confident that the productsthey have ordered are completely clean and healthy, all canteen staff members shouldmaintain consistency when it comes to proper hygiene. When it comes to the food they order,the students should pay closer attention. In order for the canteen employees to recognize theexact problem that needs to be resolved or improved, they must express their criticism of themeal that was provided to them.The Canteen Staff should maintain cleanliness in every area of the canteen, especially in thekitchen area wherein they process all the products that the students have ordered. Thestudents should be more observant when it comes to the food that they order. Administrationshould be more aware of the canteen's performance so that both parties are aware of whathas to be done.
Keywords: Hospitality Management